Pyrosequencing data analysis software: a useful tool for EGFR, KRAS, and BRAF mutation analysis - Shen Shanxiang; Qin Dahui (BMC, 2012)
Abstract Background Pyrosequencing is a new technology and can be used for mutation tests. However, its data analysis is a manual process and involves sophisticated algorithms. During this process, human errors may occur. A better way of analyzing pyrosequencing data is needed in clinical diagnostic laboratory. Computer software is potentially useful for pyrosequencing data analysis. We have developed such software, which is able to perform pyrosequencing mutation data analysis for epidermal growth factor receptor, Kirsten rat sarcoma viral oncogene homolog and v-raf murine sarcoma viral oncogene homolog B1. The input data for analysis includes the targeted nucleotide sequence, common mutations in the targeted sequence, pyrosequencing dispensing order, pyrogram peak order and peak heights. The output includes mutation type and percentage of mutant gene in the specimen. Results The data from 1375 pyrosequencing test results were analyzed using the software in parallel with manual analysis. The software was able to generate correct results for all 1375 cases. Conclusion The software developed is a useful molecular diagnostic tool for pyrosequencing mutation data analysis. This software can increase laboratory data analysis efficiency and reduce data analysis error rate. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1348911657684292.